Seniausioji lietuviu̜ literatūra - Bučys, Algimantas (Lietuvos Rašytoju̜ Sa̜jungos Leidykla, 2009)
Zsfassung in engl. und russ. Sprache. - Engl. Zsfassung u.d.T.: The ancient Lithuanian literature in the time of Mindaugas : (the polyparadigmatic research of cultural conflicts in the Middle Ages, the Lithuanian case)
Keywords: Lithuanian literature; Paganism; Christianity; Christian saints